Penerapan Metode Analytical Hierarchy Process (AHP) Dalam Menentukan Siswa Berprestasi Di SMK Negeri 6 Kota Bengkulu - Ahmad, Rahman; Yupianti, Yupianti; Beti, Ila Yati (Jurnal Media Infotama, 2024)
SMKN 6 Bengkulu City is one of the public vocational high schools in Bengkulu City. So far, the process of selecting outstanding students is only seen from the results of report cards by summing up all the grades per subject obtained by students, and then ranking them. This is certainly less effective in determining outstanding students, because it must be supported by other aspects such as the value of student attitudes during the teaching and learning process, student attendance, academic and non-academic achievements. The purpose of this research is to implement the Analytical Hierarchy Process (AHP) method in determining outstanding students at SMKN 6 Bengkulu City. Therefore, in this study an application was built that can be used as a forum in determining outstanding students at SMKN 6 Bengkulu City. The implementation of Analytical Hierarchy Process (AHP) method in determining outstanding students at SMKN 6 Bengkulu City can assist schools in determining outstanding students in every school year, where the final score will be sorted from the highest score to the lowest score to get the achievement rank of each student, where the assessment parameters/criteria used are the average report card score, attitude score, attendance percentage, number of academic achievements, and number of non-academic achievements. Based on sample data of student assessments at SMKN 6 Bengkulu City, used for calculations through the Analytical Hierarchy Process (AHP) Method for 2022/2023 Odd Period as many as 10 students of class X, the results of outstanding students were taken from the highest score, namely M. Fadhil Dwiki Rahmadan with a score of 78.31956